SISTEM PAKAR BACKWARD CHAINING UNTUK PEMILIHAN ALAT KONTRASEPSI YANG COCOK BERBASIS ANDROID - Lesmana, Lido Sabda (STKIP PGRI Sumatera Barat, 2017)
Family planning program is also one of duty and responsibility for a doctor or midwife provide the right solution for patient to get step or way in program of activity of family planning. If viewed from the rankings of the number of population density according to CIA World Factbook in 2004, Indonesia occupies the number of population most number 4 in the world with a population of 238,452,952 people. So look at the condition Family planning to aim to have two children enough is an Indonesian government program that has for years on the run. However, the most common obstacle is for the selection of steps to run the program such as Condoms, Birth Control Pills, KB Injections, IUD (Intrauterine Device) and so on. With the help of existing Android program on the smart phone will help people in getting information online whenever and wherever about the utilization and constraints faced in running the family planning program. Keywords : Family Planning, Contraception, Backward Chaining, Smart Phone